2012
DOI: 10.1016/j.pec.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making and other variables as correlates of satisfaction with health care decisions in a United States national survey

Abstract: Objective The purpose of this study was to examine the relationship between shared decision-making (SDM) and satisfaction with decision (SWD) within a larger survey of patient decision-making in health care consultations. Methods A randomly selected age-proportionate national sample of adults (aged 21–70 years) stratified on race, ethnicity, and gender (N = 488) was recruited from a health research volunteer registry and completed an online survey with reference to a recent health consultation. Measures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 11 publications
7
74
1
4
Order By: Relevance
“…Similar to the findings from studies about other populations, [263][264][265][266][267] the clinicians in this study reported that communication about ADRs was generally important in clinical practice. However, in specific cases they described filtering the information that they discussed with families.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the findings from studies about other populations, [263][264][265][266][267] the clinicians in this study reported that communication about ADRs was generally important in clinical practice. However, in specific cases they described filtering the information that they discussed with families.…”
Section: Discussionsupporting
confidence: 86%
“…35,36 Further, research suggests that SDM does not adversely affect patient outcomes 34 and may in fact improve outcomes such as adherence to treatment 21 and satisfaction with care. 20 Though past research 14,24,25 has shown an impact of personal characteristics, such as age and race, on SDM, these relationships were not significant in the present study. However, the effect sizes obtained in past research were generally small, except for marriage, which had a moderately strong relationship.…”
Section: Discussioncontrasting
confidence: 81%
“…For patients who do not have specific preferences, 19 provider consultations must provide them with enough time to explore options and match preferences to treatment. Patient perceptions about the quality of SDM can impact care outcomes, including satisfaction 20 and treatment adherence. 21 Further, patients may see a direct connection between time spent with the provider and the ability to truly share in the decision-making process.…”
mentioning
confidence: 99%
“…Therefore, SDM directly aims to increase patient knowledge. In addition, recent investigations have shown that SDM improves patient attitudes toward their disease, treatment options, and healthcare providers by increasing patient satisfaction, satisfaction with the treatment decision, patient participation, emotional status, and by reducing decisional conflict, within various decision contexts (57,(60)(61)(62)(63)(64).…”
Section: The Role For Shared Decision-makingmentioning
confidence: 99%